Avaliação de métodos laboratoriais utilizados na caracterização dos processos fermentativos em silagens - Fortes, Alessandra de Campos (2017)
The forage conservation by ensilage is a well-known process, widespread throughout the world. However, laboratory methods for evaluating silages present differences between research groups. In this context, procedures used to evaluate water soluble carbohydrates (WSC) and methods to determine ammonia nitrogen (N-NH3) were compared with the objective of optimizing the analytical routine in forage conservation laboratories. The samples used were collected from different silos, constituting four classes of silages with different fermentation profiles: corn silage (n = 20), forage peanut silage (n = 20), elephant grass silage (n = 20) and sugarcane silage (n = 20). In the first experiment, the samples were submitted to WSC evaluation, using the following methods: phenol-sulfuric acid (PSA), anthrone and phenol with water extraction (PWE). In the second experiment, the samples were submitted to N-NH3 determination, using the following methods: ammonia ion-selective electrode (ISE), phenol-hypochlorite (PH), doles® commercial kit and AOAC (Association of Official Analytical Chemists). The data were submitted to analysis of variance and the means were compared by the Student t test at 10% of probability. The anthrone and PSA methods presented similar values (P > 0.10) for WSC in all the samples evaluated. However, the PSA method proved more practical and precise (mean coefficient of variation: MCV = 0.07%). This method also presented the lowest cost per sample for the determination of WSC in the evaluated silages, when compared to anthrone (R$ 3.80 in the FAS e R$ 5.16 in the a nthrone). The PWE method overestimated (P < 0.10) the WSC values in the samples of forage peanut, elephant grass and sugarcane silages. However, there was no difference in the WSC values (P > 0.10) of corn silages. Therefore, for this silages class, the PWE method can be used in substitution for PSA, given that, for the PWE method, the extraction of WSC is done only in water, generating reagent economy (R$ 0.47 less per sample in relation to PSA, which uses 80% ethanol extraction). Regarding the values for N-NH3, the standard method was the PH method, given its practicality, precision (MCV = 1.58%) and economy (R$ 0.05 per sample). The AOAC method presented values similar (P > 0.10) to the PH method, but was less practical, less precise (MCV = 5.85%) and with higher cost per sample (R$ 2.46). The ISE method would be even more practical than PH, however, it overestimated (P < 0.10) the NNH3 values of the samples e proved to be expensive (R$ 2.27 per sample). Thus, in the present study, it was verified that the methods most indicated to determine WSC and N -NH3 in corn, forage peanut, elephant grass and sugarcane silage were respectively: PSA and PH methods, given that they present greater precision and efficacy, low cost, and have easier protocols execution, optimizing the laboratory routine for the determination of these two variables of extreme importance in the evaluation silo fermentation quality.